Mechanistic Studies with DNA Polymerases Reveal Complex Outcomes following Bypass of DNA Damage - Robert L. Eoff; Jeong-Yun Choi; F. Peter Guengerich (Journal of Nucleic Acids)
DNA is a chemically reactive molecule that is subject to many different covalent modifications from sources that are both endogenous and exogenous in origin. The inherent instability of DNA is a major obstacle to genomic maintenance and contributes in varying degrees to cellular dysfunction and disease in multi-cellular organisms. Investigations into the chemical and biological aspects of DNA damage have identified multi-tiered and overlapping cellular systems that have evolved as a means of stabilizing the genome. One of these pathways supports DNA replication events by in a sense adopting the mantra that one must “make the best of a bad situation” and tolerating covalent modification to DNA through less accurate copying of the damaged region. Part of this so-called DNA damage tolerance pathway involves the recruitment of specialized DNA polymerases to sites of stalled or collapsed replication forks. These enzymes have unique structural and functional attributes that often allow bypass of adducted template DNA and successful completion of genomic replication. What follows is a selective description of the salient structural features and bypass properties of specialized DNA polymerases with an emphasis on Y-family members.